Rating the Participation of Electricity Consumers in Demand Response Events - Silva, Catia (2020)
To successfully enable Demand Response in the energy market, the necessity for modification of the actual business models urges. The authors present innovation from previous works with a method designed to deal with the uncertainty from active consumers in Demand Response events. The proposal has three variations designed to improve the accuracy of the actual response of the consumers in the management of a local community - Basic Rate, Cost Rate and Clustering Rate Methods. The attribution of reliability rates, according to previous Demand Response events (for example, emergency events where a certain target is needed), will decide which consumers are selected for the optimal scheduling. With this, the manager entity possesses valuable information to increase profit, choosing trustworthy consumers. The methods are compared in a case study with 548 DG units and 20,310 small consumers. The results demonstrate the viability of the approach and prove that reliability rates approach is useful to deal with the uncertainty of actual response in DR events.